2021
DOI: 10.1007/s10854-021-05806-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe doping on the structural, morphological, optical, magnetic and dielectric properties of BaSnO3

Abstract: Doping at the possible A or B site in the ABO3 perovskite can alter the structural, morphological and optical properties of the compounds. Perovskite alkaline earth stannate BaSnO3 doped with Fe resulted in BaSn1-xFexO3 compounds having different concentrations (x=0.00, 0.01, 0.02, 0.03, 0.05 and 0.07) were prepared by solid-state method. The Rietveld analyzes were performed to determine the phase purity and the changes in structural parameters. Morphological analysis identifies the formation of hexagonal nano… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As the cerium content in strontium titanate increased, so did the crystallite size. 27 Since all of the cerium atoms fit inside the crystal structure of strontium titanate, the expansion of the crystallite will not be hampered by the inclusion of cerium at the A site of the perovskite matrix. Hence the crystallite size increased with an increase in cerium concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As the cerium content in strontium titanate increased, so did the crystallite size. 27 Since all of the cerium atoms fit inside the crystal structure of strontium titanate, the expansion of the crystallite will not be hampered by the inclusion of cerium at the A site of the perovskite matrix. Hence the crystallite size increased with an increase in cerium concentration.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the deposited nanoporous perovskite structures have tunable bandgap energy and have various applications in photoelectric devices. Our previous investigations reported the nonlinear optical and magnetic properties of Ni-doped, Mn-doped, and Fe-doped BaSnO 3 powder samples [ [24] , [25] , [26] ]. Further, the supercapacitor behavior of Mn-doped BaSnO 3 powders is also reported [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result clearly indicates that the oxidation state of some iron ions is reduced in the lattice, thereby balancing the charge through defects in the form of oxygen vacancies. 24,27,28 Spectral fitting could deconvolute the O 1s spectra into three peaks at the binding energies of 529.04, 530.68, and 531.60 eV (Figure 3e). The peaks at 529.04 and 531.60 eV are correlative with the lattice oxygen (O L ) and oxygen vacancies (O V ), respectively.…”
Section: ■ Introductionmentioning
confidence: 99%